Penggunaan Protein Bahan Makanan berdasarkan Keatahanan Degradasinya pada Domba - Nur Aeni Sigit (Buletin Ilmu Makanan Ternak, 1987)
The Previous in Vitro experiment indicated clearly that urea (A), peanut leaves (B), cassava leaves (C), soybean meal by product (D) and coconut oil meal (D) resulted a significant different levels of ammonia, Differences in rumen ammonia concentrations could eventually be used as an in vivo index of protein degradation value in the rumen and thus predict the amount of